ANALISIS KESENGAJAAN DALAM BENTUK TINDAK PIDANA MEMBUAT SURAT PALSU (PUTUSAN NO.61/PID.B/2022/PN JAKARTA SELATAN) : Analysis Of Deliberation In The Form Of Criminal Act Of Formulating Fake Letters (Decision No.61/Pid.B/2022/Pn Jakarta Selatan) - Rigo Ijaprana Purba; Maria Silvya Elisabeth Wangga (Faculty of Law, Universitas Trisakti, 2024)
This research relates to decision No. 61/Pid.B/2022/PN Jkt Sel. The chronology of which in this decision the defendant named Fiky Mukiandhany who was an accomplice in the crime of forgery of letters. This legal scientific work discusses issues related to how deliberate the perpetrator of the crime of making a fake letter (Decision No. 61/Pid.B/2022/PN Jkt Sel) and whether deliberate intent in the crime of making a fake letter in Decision No. 61/Pid.B/2022/PN Jkt Sel is an excuse for criminal erasure. This investigate may be a regulating and graphic legitimate inquire about utilizing auxiliary information gotten through writing ponder, the information is handled subjectively and the conclusion is drawn utilizing deductive rationale. Based on the comes about of the inquire about, it is found that the deliberately committed by the culprit of the wrongdoing of making a fake letter in Decision No. 61/Pid.B/PN Jkt Sel is purposefulness within the shape of confusion or botch, namely Misdirection of Facts (feitelijke dwaling).